A description of the mitogenome of the Endangered Taiwanese angelshark, Squatina formosa. (3rd March 2016) - Corrigan, Shannon; Yang, Lei; Cosmann, Paul J.; Naylor, Gavin J. P.
Abstract: Squatinid sharks are among the most threatened of cartilaginous fishes. Here we describe the complete mitochondrial genome sequence (16, 690 bp) of the Endangered Taiwanese angelshark, Squatina formosa . It has 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes, and 1 control region in the typical vertebrate arrangement.